Editorial - Mensah Danquah, Monica (Ghana Library Journal, 2024)
I am pleased to present Volume 29, Issue 2 of the Ghana Library Journal . This marks the sixth issue under my tenure as Editor-in-Chief, which began in July 2022. I am also delighted to share that the Ghana Library Journal has been successfully indexed in the prestigious Asian Scientific Citation Index (ASCI) Database. This accomplishment is a testament to the journal’s dedication to academic excellence and its impactful contributions to the field. I extend my deepest gratitude to the editorial board members for their unwavering support, to our diligent reviewers, and especially to our contributors for selecting this journal as a platform for their research findings.